Perbandingan Kualitas Citra Hard Copy dengan Hasil Digitizer dan Kamera Saku pada Foto Polos Tulang Belakang Spondilosis Vertebra di Bagian Radiologi RSUP dr.Sardjito - , RUFITA ISMU ASTANIA; , Dr. dr. Lina Choridah, Sp.Rad(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : Low back pain is one the highest prevalence of musculoskeletal disorder affecting the world population, and spondylosis is one of the major etiology of specific low back pain. Early diagnose of spondylosis still use the conventional plain film radiograph. The lack of radiologist in Indonesia to read the plain film can be solved by the implementation of teleradiology. Teleradiology needs a device to convert the conventional plain film to digital form, in this case it is digital camera and digitizer. Aim : Prove there is no difference in image quality and diagnose accuracy between conventional hard copy and newly digitized plain film radiograph with production house medical faculty of UGM digitizer and Sony Cyber Shot DSC-W 170 camera of spine plain film in spondylosis. Metode dan Material : This research is using analytic observational retrospective design. Samples are taken from dr.Sardjito central hospital patient with clinical symptomps of spondylosis and take spine radiology examination. Result : Based on the assessment of 30 samples, diagnostic accuracy of digitizer soft copy group p=0,18, camera soft copy group p=0,564. For the image quality, digitizer soft copy group p=0,317, camera soft copy group p<0,001. Conclusion : No statistically significant difference in diagnostic accuracy between plain film hard copy compared with digitizer and pocket camera. No statistically significant difference in image quality between plain film hard copy compared with digitizer, but there is a significant difference in image quality between plain film hard copy and camera.